Mapping 245 SSR markers on the Vitis vinifera genome: a tool for grape genetics - Adam-Blondon, A.F; Roux, C; Claux, D; Butterlin, G; Merdinoglu, D; This, P (Theoretical and applied genetics, 2004)
The aim of the present work was to develop a microsatellite marker-based map of the Vitis vinifera genome (n=19), useful for genetic studies in this perennial heterozygous species, as SSR markers are highly transferable co-dominant markers. A total of 346 primer pairs were tested on the two parents (Syrah and Grenache) of a full sib population of 96 individuals (S x G population), successfully amplifying 310 markers. Of these, 88.4% markers were heterozygous for at least one of the two parents. A total of 292 primer pairs were then tested on Riesling, the parent of the RS1 population derived from selfing (96 individuals), successfully amplifying 299 markers among which 207 (62.9%) were heterozygous. Only 6.7% of the markers were homozygous in all three genotypes, stressing the interest of such markers in grape genetics. Four maps were constructed based on the segregation of 245 SSR markers in the two populations. The Syrah map was constructed from the segregations of 177 markers that could be ordered into 19 linkage groups (total length 1,172.2 cM). The Grenache map was constructed with the segregations of 178 markers that could be ordered into 18 linkage groups (total length 1,360.6 cM). The consensus S x G map was constructed with the segregations of 220 markers that were ordered into 19 linkage groups (total length 1,406.1 cM). One hundred and eleven markers were scored on the RS1 population, among them 27 that were not mapped using the S x G map. Out of these 111 markers, 110 allowed to us to construct a map of a total length of 1,191.7 cM. Using these four maps, the genome length of V. vinifera was estimated to be around 2,200 cM. The present work allowed us to map 123 new SSR markers on the V. vinifera genome that had not been ordered in a previous SSR-based map (Riaz et al. 2004), representing an average of 6.5 new markers per linkage group. Any new SSR marker mapped is of great potential usefulness for many applications such as the transfer of well-scattered markers to other maps for QTL detection, the use of markers in specific regions for the fine mapping of genes/QTL, or for the choice of markers for MAS.